Identification of five substituted phenethylamine derivatives 5‐MAPDB, 5‐AEDB, MDMA methylene homolog, 6‐Br‐MDMA, and 5‐APB‐NBOMe. Issue 2 (9th February 2016) - Liu, Cuimei; Jia, Wei; Qian, Zhenhua; Li, Tao; Hua, Zhendong
Abstract : This paper reports analytical properties of five substituted phenethylamine derivatives seized from a clandestine laboratory. These five derivatives include 5‐(2‐methylaminopropyl)‐2, 3‐dihydrobenzofuran (5‐MAPDB, 1 ), 5‐(2‐aminoethyl)‐2, 3‐dihydrobenzofuran (5‐AEDB, 2 ), N, 2‐dimethyl‐3‐(3, 4‐methylenedioxyphenyl)propan‐1‐amine (MDMA methylene homolog, 3 ), 6‐bromo‐3, 4‐methylenedioxymethamphetamine (6‐Br‐MDMA, 4 ), and 1‐(benzofuran‐5‐yl)‐ N ‐(2‐methoxybenzyl)propan‐2‐amine (5‐APB‐NBOMe, 5 ). These compounds were identified by liquid chromatography‐quadrupole time‐of‐flight mass spectrometry (LC‐QTOF‐MS), gas chromatography‐mass spectrometry (GC‐MS), and nuclear magnetic resonance spectroscopy (NMR). No analytical properties about compounds1‐4 have appeared until now, making this the first report on these compounds. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Five substituted phenenthylamine derivatives 5‐MAPDB, 5‐AEDB, MDMA methylene homolog, 6‐Br‐MDMA, and 5‐APB‐NBOMe were identified using LC‐QTOF‐MS, GC‐MS and NMR.